The heterogeneity of aqueous solutions: the current situation in the context of experiment and theory - Stepanov, German O.; Penkov, Nikita V.; Rodionova, Natalia N.; Petrova, Anastasia O.; Kozachenko, Angelina E.; Kovalchuk, Alexander L.; Tarasov, Sergey A.; Tverdislov, Vsevolod A.; Uvarov, Alexander V. (Frontiers in Chemistry, 2024)
The advancement of experimental methods has provided new information about the structure and structural fluctuations of water. Despite the appearance of numerous models aimed at describing a wide range of thermodynamic and electrical characteristics of water, there is a lack of a systemic understanding of structuring in aqueous solutions. A particular challenge is the fact that even pure water is a heterogeneous, multicomponent system composed of molecular and supramolecular structures. The possibility of the existence and nature of such structures is of fundamental importance for various fields of science. However, great difficulties arise in modeling relatively large supramolecular structures (e.g., extended hydration shells), where the bonds between molecules are characterized by low energies. Generally, such structures may be non-equilibrium but relatively long-lived. Evidently, short times of water microstructure exchanges do not mean short lifetimes of macrostructures, just as the instability of individual parts does not mean the instability of the entire structure. To explain this paradox, we review the data from experimental and theoretical research. Today, only a part of the experimental results on the lifetime of water structures have been confirmed by modeling, so there is no complete theoretical picture of the structure of water yet. We propose a new hierarchical water macrostructure model to resolve the issue of the stability of water structures. In this model, the structure of water is represented as consisting of many hierarchically related levels (stratification model). The stratification mechanism is associated with symmetry breaking at the formation of the next level, even with minimal changes in the properties of the previous level. Such a hierarchical relationship can determine the unique physical-chemical properties of water systems and, in the future, provide their complete description.